Prospective individual patient data meta-analysis of two randomized trials on convalescent plasma for COVID-19 outpatients - Millat-Martinez, Pere; Gharbharan, Arvind; Alemany, Andrea; Rokx, Casper; Geurtsvankessel, Corine; Papageorgiou, Grigorios; van Geloven, Nan; Jordans, Carlijn; Groeneveld, Geert; Swaneveld, Francis; van der Schoot, Ellen; Corbacho-Monné, Marc; et al. (Nature communications, 2022)
Data on convalescent plasma (CP) treatment in COVID-19 outpatients are scarce. We aimed to assess whether CP administered during the first week of symptoms reduced the disease progression or risk of hospitalization of outpatients. Two multicenter, double-blind randomized trials (NCT04621123, NCT04589949) were merged with data pooling starting when <20% of recruitment target was achieved. A Bayesian-adaptive individual patient data meta-analysis was implemented. Outpatients aged ≥50 years and symptomatic for ≤7days were included. The intervention consisted of 200–300mL of CP with a predefined minimum level of antibodies. Primary endpoints were a 5-point disease severity scale and a composite of hospitalization or death by 28 days. Amongst the 797 patients included, 390 received CP and 392 placebo; they had a median age of 58 years, 1 comorbidity, 5 days symptoms and 93% had negative IgG antibody-test. Seventy-four patients were hospitalized, 6 required mechanical ventilation and 3 died. The odds ratio (OR) of CP for improved disease severity scale was 0.936 (credible interval (CI) 0.667–1.311); OR for hospitalization or death was 0.919 (CI 0.592–1.416). CP effect on hospital admission or death was largest in patients with ≤5 days of symptoms (OR 0.658, 95%CI 0.394–1.085). CP did not decrease the time to full symptom resolution. Trial registration: Clinicaltrials.gov NCT04621123 and NCT04589949. Registration: NCT04621123 and NCT04589949 on https://www.clinicaltrials.gov Clinical studies have suggested that the therapeutic potential of polyclonal convalescent plasma is highest in the first days of symptoms. Here, the authors present results from a pooled analysis of two clinical trials in COVID-19 outpatients that did not provide conclusive evidence in favor of convalescent plasma.